The impact of Gaza war: online educational challenges and mental health of university students - Basel El-Khodary; Sanaa Aboudagga (Middle East Current Psychiatry)
Abstract Background Universities in the Gaza Strip have demonstrated exceptional resilience by resuming distance learning despite the ongoing challenges resulting from the Israeli war following the events of October 7, 2023. This study aims to identify the primary obstacles students face in accessing and participating in online learning under these conditions, and to examine the relationship between these educational challenges and students’ mental health. The sample consists of 150 university students studying online. Educational challenges scale and Depression Anxiety Stress Scale were used. Results The findings indicated that students encountered difficulties obtaining basic necessities and stable internet, which affected their ability to participate in online learning. Statistical analyses revealed that higher levels of educational challenges—particularly related to adversity, internet access, and managing online resources—were strong predictors of increased anxiety and depression symptoms. Housing destruction was also significantly associated with heightened anxiety. Conclusions The results underscore the close link between educational barriers and mental health outcomes during conflict. Serval recommendations were suggested by the researchers.